Balinese Cultural Continuity: Heroine’s Role in Luh Ayu Manik Mas at War with the Spirit World - Yanuaresti Kusuma Wardhani; Yudhanita Pertiwi; Estrella T. Arroyo; Nurhadianty Rahayu; Zahratul Umniyyah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research explores the role of the heroine in preserving Balinese cultural identity, focusing on the character of Luh Ayu Manik Mas from the children's story, "At War with the Spirit World." By employing Roland Barthes's mythological analysis, we delve into the denotative and connotative meanings embedded within the narrative. Denotatively, the heroine is portrayed as an independent and strong figure, essential for cultural continuity. She actively engages in preserving Balinese traditions, such as participating in water rituals and protecting the environment. Connotatively, the heroine embodies qualities of bravery, sacrifice, and a deep connection to Balinese cultural values. Her actions highlight the significance of environmental sustainability and the preservation of cultural heritage in the face of modern challenges. By analyzing the character of Luh Ayu Manik Mas, this research demonstrates how literature can contribute to the maintenance of cultural identity. The heroine's journey serves as a powerful tool for transmitting cultural values and inspiring future generations to embrace and preserve Balinese traditions.